Potência anaeróbica e distâncias percorridas durante jogos em jovens atletas de futebol nas categorias Sub-15 e Sub-17 - Silva, Leandro Lima; Paulucio, Dailson; Paulucio, Dailson; Pompeu, Fernando A. M. S.; Pompeu, Fernando A. M. S.; Alonso, Luciano; Alonso, Luciano; Godoy, Erik Salum de; Godoy, Erik Salum de; Bezerra, Lucas; Bezerra, Lucas; Lima, Vicente; et al. (Revista de Educação Física / Journal of Physical Education, 2017)
Introdução: O desenvolvimento dos aspectos fisiológicos do desempenho de atletas de futebol é importante para os treinadores e cientistas, que devem ter compreensão sobre as interações complexas de múltiplos fatores. Objetivo: Comparar as intensidades de deslocamento do jogo de futebol e os resultados do teste de potência anaeróbica entre atletas jovens de futebol nas categorias Sub-15 e Sub-17. Métodos: Foram avaliados 31 atletas (14 atletas da Sub-15 e 17 da Sub-17). As distâncias percorridas nos jogos foram mensuradas pelo sistema de posicionamento global (GPS-QSTARZ-5Hz) e a potência anaeróbica foi avaliada pelo teste de Yo-yo Recovery 2. A maturação sexual foi avaliada utilizando metodologia de autoanálise. Resultados: Os atletas Sub-17 obtiveram melhores resultados nas distâncias percorridas em diferentes velocidades: DP>10km/h (1891,57m + 591,38m vs 2626,52m + 889,49m; p=0,013); DP≤10km/h (5738,00m + 825,37m vs 6334,47m + 710,17m; p=0,039); DTP (7629,57m + 1088,69m vs 8961,00m + 1143,30m; p=0,003) e na potência aeróbica (448,57m + 118,63m vs 767,05m+240,92m; p<0,001). Não houve diferença maturacional entre os grupos (p=0,10). Conclusão: De modo geral, os atletas Sub-17 apresentaram maior capacidade de manter o desempenho do que os da Sub-15 tanto nas distâncias percorridas em diferentes velocidades durante os jogos, quanto no teste de potência anaeróbica, mesmo não havendo diferenças maturacionais. Recomenda-se atenção especial ao escalar grande parte do time da categoria Sub-17 transpondo atletas da Sub-15. Anaerobic power and distances during games in young soccer athletes in the Sub-15 and Sub-17 categories Introduction: The development of the physiological aspects of soccer athletes' performance is important for coaches and scientists, who must have understanding about the complex interactions of multiple factors. Objective: To compare the displacement intensities of the soccer game and the results of the anaerobic power test among young soccer athletes in the Sub-15 and Sub-17 categories. Methods: The distances covered in the games were measured by the global positioning system (GPS-QSTARZ-5Hz) and the anaerobic power was evaluated by the Yo-yo Recovery 2 test. And sexual maturation was evaluated through a self-assessment.Objective: To compare the displacement intensities of the soccer game and the results of the anaerobic power test among young soccer athletes in the Sub-15 and Sub-17 categories. Results: Results: Sub-17 athletes obtained better results in distances traveled at different speeds: DP> 10km / h (1891.57m + 591.38m vs 2626.52m + 889.49m; p = 0.013); DP≤10km / h (5738.00m + 825.37m vs 6334.47m + 710.17m; p = 0.039); DTP (7629.57m + 1088.69m vs 8961.00m + 1143.30m, p = 0.003) and aerobic power (448.57m + 118.63m vs 767.05m + 240.92m, p <0.001). There was no maturational difference between groups (p = 0.10). Conclusion: In general, Sub-17 athletes had a better ability to maintain performance than those of Sub-15 in both the distances traveled at different speeds during the games and in the anaerobic power test, even though there were no maturational differences. Special attention is given to climbing a large part of the Sub-17 team transposing Sub-15 athletes. The abstract should not exceed 250 words and must summarize the work, giving a clear indication of the conclusions contained therein. It should be structured. The introduction should contextualize the problem.